The Importance of Change Agent Teachers Program(PPGP) in Enhancing Leadership Competencies and Skills - Hasanah, Cucun; Dikdik, Asep (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
This research is motivated by the urgency to enhance the quality of education through the development of Change Agent Teachers competencies. The aim of this study is to examine the role of teacher leadership programs in enhancing the leadership competencies of educators in Cileunyi District. This research employs a qualitative approach with a descriptive method. Data collection for this study uses interview techniques with research subjects who are teachers who have participated in the Change Agent Teachers Program. The results of this study indicate that the program not only enhances individual capabilities but also contributes to broader transformations in the learning environment. The program also successfully fosters better collaboration among teachers and enhances innovation in teaching methods. Furthermore, the research findings also show that teachers who participated in this program demonstrate improved abilities in classroom management and the use of technology in teaching. The effectiveness of this program is evident in the significant improvement of teachers' leadership competencies, shaping educators who excel not only in teaching but also in leading positive transformations in the education system. Thus, Change Agent Teachers can be considered significant catalysts of significant change in improving the quality of education at the local level.